Analysis of the Influence of Price Perception, Service Quality, and Advertising on Smartphone Purchasing Decisions at M-CEL OESAPA, Kupang City - Damaris Y. Koli; Endang Damaris Koli; Alfred G.O. Kase; Godlief F. Neonufa (Lembaga Bale Literasi, 2025)
This study is entitled